2015
DOI: 10.1016/j.bbapap.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry-based characterization of endogenous peptides and metabolites in small volume samples

Abstract: Technologies to assay single cells and their extracellular microenvironments are valuable in elucidating biological function, but there are challenges. Sample volumes are low, the physicochemical parameters of the analytes vary widely, and the cellular environment is chemically complex. In addition, the inherent difficulty of isolating individual cells and handling small volume samples complicates many experimental protocols. Here we highlight a number of mass spectrometry (MS)-based measurement approaches for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 106 publications
0
18
0
Order By: Relevance
“…Thus, a successful single cell analytical technique should provide a low absolute detection limit, a high dynamic range, and multiplexed coverage of analyte classes. 5 Mass spectrometry (MS) has become a versatile and robust method for performing volume-limited biological measurements. Mass spectrometry imaging (MSI) is at the forefront of MS-based, label-free platforms for analyzing single cells, 6,14-18 demonstrating cellular and subcellular spatial resolution 19-21 and untargeted detection of biological molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a successful single cell analytical technique should provide a low absolute detection limit, a high dynamic range, and multiplexed coverage of analyte classes. 5 Mass spectrometry (MS) has become a versatile and robust method for performing volume-limited biological measurements. Mass spectrometry imaging (MSI) is at the forefront of MS-based, label-free platforms for analyzing single cells, 6,14-18 demonstrating cellular and subcellular spatial resolution 19-21 and untargeted detection of biological molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported integration of on-line analysis of perfusates to monitor cellular secretions on chips [21, 22]. Immunoassay [2325] or enzyme assay [2628] with fluorescent detection, capillary electrophoresis with electrochemical detection [29], and enzyme assay with chemiluminescent detection [30] have all been used.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional MS approaches to cell analysis were restricted to a population of cells (such as cell lysate), where an averaged result is obtained. Recent advancements in high mass resolution MS has allowed for the confident assignment of large numbers of molecules, 15 and improved sensitivity enables MS to be applied at the single cell level, mostly in the field of metabolomics, 14 and potentially single cell peptidomics 16 and proteomics. 17 Current SCMS techniques can be broadly categorized into nonambient and ambient techniques, based on their sampling environment.…”
mentioning
confidence: 99%